Criminal Penalties against individuals and the problems of execution according to the basic system of the international criminal court - Jassim, Firas; Assi, Esraa (Journal of Legal Sciences, 2022)
The international community has  sought to establish a judicial institution that works to apply the law fairly، as a result of a necessity dictated by the circumstances of the international community، and Because of the great violations against humanity in times of peace and war، and in order to establish the parameters of international criminal justice between all societies and countries، this necessity resulted in the idea of ​​establishing an international criminal court . A court that enjoys independence and impartiality  exercising  its international jurisdiction according to legal procedures to suo any one  accused of committing an international crime in to inflict Penalties against him or her، whether (individuals or countries). But when execution these penalties may result in some symptoms or problems that hinder the application of what the court has ruled، as a result of wrong or abusive implementation against the victim or the convicted person، which requires solving that problem in accordance with  a specific mechanism decided by that system.